Nurses' knowledge and attitudes about dementia care: Systematic literature review - Evripidou, Melina; Charalambous, Andreas; Middleton, Nicos; Papastavrou, Evridiki (My University, 2019)
Purpose: To explore nurse's knowledge and attitudes toward the care of people with dementia. Design and Methods: A systematic review informed by the PRISMA-P (preferred reporting items for systematic reviews and meta-analyses protocols) guidelines in four databases (CINAHL, PsyINFO, Pubmed, Cohrane, EMBASE) using keywords “attitudes,” “behaviors,” “dementia,” “knowledge,” and “nurses.” Predetermined inclusion criteria were selected. The review was conducted between January 1 and December 30, 2017. Findings: Sixteen quantitative studies, one qualitative, and two mixed methods studies were included. Nurses lack knowledge, communication skills, management strategies, and confidence in the provision of dementia care. Interventional studies suggested that knowledge and attitudes improved after training programs were implemented. Practice Implication: This review contributes to care advancement and practice development through the reinforcement of organizational support and educational opportunities for nurses.
Keywords: Attitudes; Dementia; Knowledge; Nurses